Analysis of the current scenario of Compressed Earth Block (CEB) production - Antonelli, Jeferson Fernando Corrêa; Azambuja, Maximiliano dos Anjos (National Journal of City Management, 2021)
The main objective of this study is to identify the parameters that influence the quality of the production of compressed earth blocks (CEB). Thus, an analysis of the performance of the materials that make up the final product was carried out, such as the binders that act as chemical stabilizers and the different types of soils, also the mechanical resistance and durability tests and finally the technical standards for its manufacturing. For this aim, a literature review was carried out in three electronic databases, Scopus, Web of Science and Scielo. The results showed environmental concerns with the use of Portland cement for stabilization, therefore, 18% of the studies used agricultural residues and 25% used mineral by-products, for partial or total replacement of Portland cement. Soils with plasticity indexes between 15% and 30% have a stabilization success rate of 69%, while soils with plasticity index less than 15% have a stabilization greater than 93%, which can be increased to 100% if the soil have a percentage of clay and silt between 21 and 35%. On the other hand, a plasticity index above 30% negatively affects stabilization. The compaction energy applied in the manufacture of CEB is an important parameter, as it influences the density, thermal conductivity and mechanical strength. Among the sustainable construction techniques, CEB is a great option, as it can be done locally and with ease of construction.